When the Cat's Away, the Mice Will Play: Gambling Behaviour of Visitors in Australia - Bin Dong; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2010)
What happens if national legal laws or enforcements and social norms are no longer able to directly regulate individual behaviour? According to our knowledge, not much empirical evidence has emerged answering such a seemingly simple question. The challenge is to distinguish between the effects of social norm and of legal enforcement. One way to explore such a question in an almost natural quasi-experimental setting is to focus on tourists' behaviour. Tourists are visiting another country for a relatively short period of time and are acting in a different (legal) environment where formal and informal rules are different to those found in their own country. Using data from Australia we focus on gambling activities since these are prohibited in some countries. We find that tourists from countries where gambling is prohibited spend a significantly larger share of their entertainment expenditure on gambling than those who come from countries where gambling is legalized. Thus, gambling increases ("mice play") without legal enforcement ("when the cat is away"). It is also noteworthy that there seems to be a lack of internalized social norms that would prevent tourists from partaking in these gambling activities.
Keywords: A13; K42; L82; 330; gambling; legal enforcement; social norms